(untitled) (Journal of Dhaka National Medical College & Hospital, 2017)
Background: Uric acid is an independent risk factor for cardiovascular disease. At present, Coronary artery disease (CAD) in one of the leading cause of death in the worldwide also in Bangladesh. Although studies were conducted abroad regarding association of scrum uric acid with in hospital out comes in patient with acute coronary syndrome. No data is yet available to show the association in our country. Objectives: The objective of the study was to assess the association of serum uric acid level on admission with in hospital outcomes of the patient, with acute coronary syndrome. Materials and Methods: This study was carried out in the department of cardiology, Dhaka National Medical Institute Hospital, Dhaka from October, 2014 to September 2015. In this case series study. 102 diagnosed Patients of acute coronary syndrome free from gout, renal disease, hepatic disorder and other malignant conditions were enrolled by non random sampling. Serum uric acid of all subject was measured within 24 hours of presentation. During hospital stay the outcome (good and bad) were observed in all subjects. Result: Patients with higher serum uric acid (SUA>6.5mg%, Group-II) were compared with patients with lower serum uric acid (SUA<6.5mg%, Group-1). In Group I (n=60), good recovery, morbidity and mortality were found in 43 (65.2%), 21 (31.8%), 2 (3.0%) Patients and in Group II (n=42), good recovery, morbidity, mortality were 13 (31%), 23 (54.8%) and 6 (14.3%) patients respectively. In group II Patients having high Scrum uric acid concentration had low good recovery but high morbidity and mortality compared to group 1 Patients. In group I (n=60), good outcome and bad outcome was found in 43 (65.2%), and 23(34.8%) patients and in group II (n-42), those were in 13 (31%) and 29 (69%) patents. Logistic regression analysis of scrum uric acid concentration of study subjects were done considering uric acid as independent variable but outcome as dependent variable. It was shown that the odds ratio of mortality was 5.38 (95% CI p<0.007), odds ratio of morbidity was 4.10 (95% CI p<0.001) and odds ratio of bad outcome was 4.67 (95% CI p<0.001). This finding indicates a patient having high uric acid had 5.38 times increased bad outcome that patients having low serum uric acid concentration. Conclusion: On admission serum uric acid estimation is a good predictor of in hospital bad outcome in patients with acute coronary syndrome. As it is a cheap and noninvasive procedure, it can be routinely practiced in cardiac emergency department for risk stratification of patients. J. Dhaka National Med. Coll. Hos. 2017; 23 (02): 42-46